Mali: patterns and limits of donor-driven ownership - Isaline Bergamaschi (University of Oxford, Global Economic Governance Programme (GEG), 2007)
Mali is a landlocked country in francophone West Africa that ranked 175th (out of 177) in the United Nations Human Development Index in 2006. Its economy is mostly based on agriculture, and is marked by a high dependence on external assistance. However, the democratization process began in 1991, and the country has recently enjoyed relative social and political stability. Some players on the ground describe Mali as an example of "donor-driven ownership", meaning that there are few signs of genuine policy ownership and leadership in aid relationships, and that the country lacks both "capacity" and "political will" to enable it to reach its development goals. This chapter argues that as aid-donors' influence over policy has increased, the nation's capacity and will to take the lead in managing aid and the aid relationship have decreased. Indeed, if the current political situation seems characterized by a certain degree of inertia, a lack of development strategy, weak capacities and compliance with donors, it can only be understood as the result of the weakening of the state and donor entanglement in national institutions and politics, and several decades of aid dependence. However, negotiations over economic or political reform still occur between the government and donors, sometimes in conflicting terms. These occasions reveal that the Malian government's room to manoeuvre and resources to oppose donor demands do exist, but they are limited. The chapter is divided into three main parts. The first part describes the mechanisms and path of aid-dependence. The second part assesses the impact of the implementation of the "new" aid paradigm on the possibility for recipient ownership. Indeed, the aid system and relationships must be considered in a dynamic manner, as Mali is now the "laboratory" for the implementation of the Paris declaration in West francophone Africa. The last part of the chapter unveils the conditions and potential for recipient ownership and donor support in aid relationships by building on specific policy analysis in the sector of decentralisation and the privatization of cotton.
Keywords: 330